Bioindustrial manufacturing readiness levels (BioMRLs) as a shared framework for measuring and communicating the maturity of bioproduct manufacturing processes. (23rd September 2022) - Smanski, Michael J; Aristidou, Aristos; Carruth, Ryan; Erickson, John; Gordon, Mark; Kedia, Sandeep B; Lee, Kelvin H; Prather, Darcy; Schiel, John E; Schultheisz, Heather; Treynor, Thomas P; Evans, Steven L; et al.
Abstract: Readiness level (RL) frameworks such as technology readiness levels and manufacturing readiness levels describe the status of a technology/manufacturing process on its journey from initial conception to commercial deployment. More importantly, they provide a roadmap to guide technology development and scale-up from a ''totality of system'' approach. Commercialization risks associated with too narrowly focused R&D efforts are mitigated. RLs are defined abstractly so that they can apply to diverse industries and technology sectors. However, differences between technology sectors make necessary the definition of sector specific RL frameworks. Here, we describe bioindustrial manufacturing readiness levels (BioMRLs), a classification system specific to bioindustrial manufacturing. BioMRLs will give program managers, investors, scientists, and engineers a shared vocabulary for prioritizing goals and assessing risks in the development and commercialization of a bioindustrial manufacturing process.